Inner AABB For Distance Computation In Collision Detection - Hamzah Asyrani, Sulaiman; Abdullah, Bade; Mohd Harun, Abdullah (Penerbit UTM Press, 2016)
Distance computation technique is one of the important elements for completing narrow phase collision detection system. Checking an accurate distance between two piece of polygons (or some researchers named it as primitives/triangles) is always a challenging tasks where it involves two common measurements, which is speed of the distance checking and the accuracy of the distance itself. In this paper, we performed an experiment using our latest technique called Inner AABB of Dynamic Pivot Point (DyOP) where it’s tremendously reduced number of testing and increase the speed of the distance computation. Based on the analyzed results, we believed that our technique is superior compared to other techniques in term of the speed of the detection.